2001
DOI: 10.1007/3-540-45468-3_100
|View full text |Cite
|
Sign up to set email alerts
|

Q-MAF Shape Decomposition

Abstract: Abstract. This paper address the problems of generating a low dimensional representation of the shape variation present in a set of shapes represented by a number of landmark points. First, we will present alternatives to the featured Least-Squares Procrustes alignment based on the L∞-norm and the L1-norm. Second, we will define a new shape decomposition based on the Maximum Autocorrelation Factor (MAF) analysis, and investigate and compare its properties to the Principal Components Analysis (PCA). It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Switzer suggests that we estimate Σ ∆ for a shift in lag 1. Blind source separation by independent components analysis using the Molgedey-Schuster (MS-ICA) algorithm [12] is equivalent to MAF [3]. The purpose of this algorithm is to separate independent signals from linear mixings.…”
Section: Maximum Autocorrelation Factorsmentioning
confidence: 99%
“…Switzer suggests that we estimate Σ ∆ for a shift in lag 1. Blind source separation by independent components analysis using the Molgedey-Schuster (MS-ICA) algorithm [12] is equivalent to MAF [3]. The purpose of this algorithm is to separate independent signals from linear mixings.…”
Section: Maximum Autocorrelation Factorsmentioning
confidence: 99%
“…When maximising autocorrelation the MNF analysis qualifies as an Independent Components Analysis (ICA) similar to the Molgedy-Schuster algorithm [14], see [5]. A comparative study of the PC and MNF can be found in [15,16].…”
Section: Minimum Noise Fractions Transformationmentioning
confidence: 99%
“…One example is the Active Appearance Models (AAMs) [1,2]. Applications of AAMs include recovery and variation analysis of anatomical structures in medical images, such as magnetic resonance images (MRIs) [3], radiographs [4,5] and ultrasound images [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because imaged phenomena often exhibit some sort of spatial coherence spatial autocorrelation is often a better optimality criterion than variance. We have previously adapted the MAF transform for analysis of tangent space shape coordinates [3]. In [4] the noise adjusted PCA or the minimum noise fraction (MNF) transformations were used for decomposition of multispectral satellite images.…”
Section: Introductionmentioning
confidence: 99%